Access, charge and quality of tele-dermatology e-consults in China: A standardized patients study. (November 2022) - Guo, Rui; Hou, Mengchi; Han, Yangyang; Feng, Xing Lin
Objective: Direct-to-consumer telemedicine is rapidly changing the way that patients seek medical care. This study provided the first report on access, cost and quality of text- and image-based tele-dermatology e-consults, in China. Methods: We adopted the Standardized Patients approach to evaluate the services of tele-dermatology e-consults in two metropolitan cities, that is, Beijing and Hangzhou, in China. We measured quality from four dimensions: service process, diagnosis accuracy, prescription and treatment comprehensiveness, based on China's national clinical guidelines. We performed logistic regressions to investigate factors that were associated with high-quality care. Results: For 114 physicians eligible for inclusion, we succeeded in 87 (76%) validated visits. The median waiting time was 100 minutes (IQR 19–243 minutes) and the median length of consultation was 636 minutes (about 10 hours, IQR 188–1528 minutes). Per visit costs varied from $0 to $38, with a median of $8 (IQR 4–9). Among all, 15% of visits showed high quality in service process, 84% arrived in the correct diagnosis, 24% provided high-quality prescriptions and 71% provided comprehensive treatment. Providing images was associated with high quality in service process (OR 7.22, 95% CI 1.49–34.88). Visits in metropolitan Beijing and on non-work days had better prescription quality than that in metropolitan Hangzhou (OR 6.05, 95% CI 1.75–20.95) and that on workdays (OR 3.75, 95%CI 1.27–11.04), respectively. Conclusions: Tele-dermatology e-consults seem to be easy to access and less expensive in China. However, great efforts are warranted to ensure that service processes and prescriptions adhere to clinical guidelines.